2017
DOI: 10.1902/jop.2016.160216
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health‐Related Quality of Life Before and After Treatment of Dentin Hypersensitivity With Cyanoacrylate and Laser

Abstract: There was a reduction in the impact of DH on the quality of life of study participants after interventions with laser and cyanoacrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Although the risk factors associated with hypersensitivity have been established in many studies, its impact on daily living is much less understood . Consistent with previous research, our findings that both hypersensitivity and dentine exposure are associated with difficulty eating, feeling tense and experience pain more frequently than those without these conditions highlight the relevance to the patients and could have a significant psychological impact on everyday living . For example, Beks et al showed that among a group of patients who sought treatment for dentine hypersensitivity, the impact of this condition on oral health‐related quality of life was similar to that reported by patients who suffer from TMJ disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the risk factors associated with hypersensitivity have been established in many studies, its impact on daily living is much less understood . Consistent with previous research, our findings that both hypersensitivity and dentine exposure are associated with difficulty eating, feeling tense and experience pain more frequently than those without these conditions highlight the relevance to the patients and could have a significant psychological impact on everyday living . For example, Beks et al showed that among a group of patients who sought treatment for dentine hypersensitivity, the impact of this condition on oral health‐related quality of life was similar to that reported by patients who suffer from TMJ disorders.…”
Section: Discussionsupporting
confidence: 89%
“…[23][24][25][26] Consistent with previous research, 23 our findings that both hypersensitivity and dentine exposure are associated with difficulty eating, feeling tense and experience pain more frequently than those without these conditions highlight the relevance to the patients and could have a significant psychological impact on everyday living. [23][24][25] For example, Beks et al 24 showed that among a group of patients who sought treatment for dentine hypersensitivity, the impact of this condition on oral health-related quality of life was similar to that reported by patients who suffer from TMJ disorders. This emphasises that, although oral pain may be experienced in different forms, its impact may on quality of life cannot be overlooked, especially by oral healthcare professionals who may underestimate its effect on patients' lives.…”
Section: Ta B L Esupporting
confidence: 90%
“…DH is part of everyday life for many people and can compromise their well-being. 19,20 The DHEQ-15 instrument was developed in order to quantify the effects of DH on everyday life. 8 It was aimed to provide the first cross-cultural adaptation of the DHEQ-15 in Brazil, and the findings showed the reliability and validity of the DHEQ-15 to measure the impact of DH in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of oral health‐related quality of life (OHRQoL) can complement normative measures, and a number of assessment tools have been developed with this purpose (Locker & Allen, ). One such assessment tool is the Oral Health Impact Profile (OHIP‐14; Slade, ), which has been widely used in dentistry (Lima et al., ; Liu, McGrath, & Cheung, ; Wagner et al., ), in different populations including young adults (Maida, Marcus, Spolsky, Wang, & Liu, ; Siluvai et al., ), and already used as instrument for aesthetic matters (Nicolaisen, Bahrami, Schropp, & Isidor, ; Santa‐Rosa et al., ; Silvola et al., ). This measure has been translated to Brazilian Portuguese and validated for use on the Brazilian population (De Oliveira & Nadanovsky, ).…”
Section: Introductionmentioning
confidence: 99%